Upper Bounds for Randic Spread - Gomes, Helena (2014)
The Randi´c spread of a simple undirected graph G, sprR(G), is equal to the maximal difference between two eigenvalues of the Randi´c matrix, disregarding the spectral radius [Gomes et al., MATCH Commun. Math. Comput. Chem. 72 (2014) 249–266]. Using a rank-one perturbation on the Randi´c matrix of G it is obtained a new matrix whose matricial spread coincide with sprR(G). By means of this result, upper bounds for sprR(G) are obtained.